Brokering Transnational Flows of Care: The Case of Citizen Aid. Issue 2 (14th March 2020) - Fechter, Anne-Meike
ABSTRACT: A Cambodian town is the site of transnational flows of resources between private donors, and Cambodians in need of assistance. Such forms of 'citizen aid', initiated by individuals, constitute a form of resource transfer across borders which falls outside the purview of migration scholars. Unlike remittances, they are not primarily channelled through kin-related or geographical ties. Instead, they are enabled by brokers of care, Cambodian and international, who facilitate both personal connections and forms of support. The lens of the broker enables an understanding of citizen aid as a form of brokering care. It offers a critique of the moral ambiguity of the broker, as well as on the relationship between care and control. Casting people in need not merely as recipients, but as providing opportunities for intervention sought after by supporters, means upending conventional notions of who are recipients and donors, and what kind of resources they control respectively.